2022
DOI: 10.1038/s41467-022-32770-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatially patterned hydrogen peroxide orchestrates stomatal development in Arabidopsis

Abstract: Stomatal pores allow gas exchange between plant and atmosphere. Stomatal development is regulated by multiple intrinsic developmental and environmental signals. Here, we show that spatially patterned hydrogen peroxide (H2O2) plays an essential role in stomatal development. H2O2 is remarkably enriched in meristemoids, which is established by spatial expression patterns of H2O2-scavenging enzyme CAT2 and APX1. SPEECHLESS (SPCH), a master regulator of stomatal development, directly binds to the promoters of CAT2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…This phenomenon indicates that light, when not directly participating in photosynthesis due to its inhibition by DCMU, plays a negative role in plant growth. Previous work in Arabidopsis ( Arabidopsis thaliana ) showed that DCMU treatment significantly increased the production of hydrogen peroxide (H 2 O 2 ) in the presence of light (Shi et al ., 2022), which may decrease the growth of photoheterotrophic duckweed. Under mixotrophic conditions, duckweed used both CO 2 fixation and exogenous glucose as carbon resources, and grew much faster than in any other mode (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon indicates that light, when not directly participating in photosynthesis due to its inhibition by DCMU, plays a negative role in plant growth. Previous work in Arabidopsis ( Arabidopsis thaliana ) showed that DCMU treatment significantly increased the production of hydrogen peroxide (H 2 O 2 ) in the presence of light (Shi et al ., 2022), which may decrease the growth of photoheterotrophic duckweed. Under mixotrophic conditions, duckweed used both CO 2 fixation and exogenous glucose as carbon resources, and grew much faster than in any other mode (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SnRK1 is an evolutionarily conserved protein sensor kinase that plays critical roles in plant stress responses by regulating enzyme activities and gene expression. Low energy‐ and oxidation stresses (H 2 O 2 ) trigger the relocation of KIN10 to the nucleus (Ramon et al ., 2019; Shi et al ., 2022). A long‐standing question for SnRK1 signaling is how under energy‐deficient conditions activated SnRK1 becomes translocated into the nucleus where it regulates gene expressions to reprogram cellular metabolism and restore the energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that the slow growth rates observed in meristemoids are caused by similar metabolic remodeling. Notably, a recent report (Shi et al, 2022) showed that meristemoids have elevated levels of hydrogen peroxide (H2O2), partly due to SPCH-driven repression of H 2 O 2 -scavenging enzymes CAT2 and APX1. As hydrogen peroxide is also a byproduct of oxidative phosphorylation (Wong et al, 2017), future work should explore a potential link between oxidative phosphorylation and stomatal development.…”
Section: Discussionmentioning
confidence: 99%